Altered activity of the medial prefrontal cortex and amygdala during acquisition and extinction of an active avoidance task - Jiao, Xilu; Beck, Kevin D.; Myers, Catherine E.; Servatius, Richard J.; Pang, Kevin C. (Frontiers in Behavioral Neuroscience, 2015)
Altered medial prefrontal cortex (mPFC) and amygdala function is associated with anxiety-related disorders. While the mPFC-amygdala pathway has a clear role in fear conditioning, these structures are also involved in active avoidance. Given that avoidance perseveration represents a core symptom of anxiety disorders, the neural substrate of avoidance, especially its extinction, requires better understanding. The present study was designed to investigate the activity of mPFC and amygdala neurons during acquisition and extinction of lever-press avoidance in rats. In particular, neural activity was examined in the mPFC, intercalated cell clusters (ITCs), lateral (LA), basal (BA) and central (CeA) amygdala, at various time points during acquisition and extinction, using induction of the immediate early gene product, c-Fos. Neural activity was greater in the mPFC, LA, BA, and ITC during the extinction phase as compared to the acquisition phase. In contrast, the CeA was the only region that was more activated during acquisition than during extinction. Our results indicate that elevated activity in the mPFC, BA, LA and ITCs, and reduced CeA activity is associated with extinction of active avoidance. Moreover, inhibitory neurons are activated differently in the mPFC and BA during early and late phase of acquisition and extinction, suggesting their dynamic involvement in the development of avoidance response. Together, these data start to identify the key brain regions important in active avoidance behavior, areas that could be associated with avoidance perseveration in anxiety disorders.